Parigi Carbonate Reservoir for Underground Gas Storage in West Java, Indonesia - Edison Gunawan Sirodj; Edy Sunardi; Billy G Adhiperdana; Iyan Haryanto (Geological Agency, 2022)
DOI:10.17014/ijog.9.2.219-228This paper focuses on the characteristics and distribution of shallow reservoir carbonate in an underground gas storage. This study was done on Parigi carbonate as a significant reservoir carbonate in West Java Basin. The carbonate is abundant, and it occurs at shallow depths 800 to 1000 m below sea level. This formation broadly spreads out in onshore and offshore West Java areas as platform and build-up carbonates. The development of buildup carbonates is mostly in a low relief offshore. They well-developed onshore where the build-up exhibits coral reef frameworks, high relief, reaching over 450 m in thickness. The carbonate outcrop in Palimanan, western Cirebon which has been studied is grouped into four types of lithofacies. The preservation condition of this carbonate reservoir is important, for the storage capacity can inject a big gas volume. The porosity and permeability parameters are the most influential factor in reservoir evaluation. The parameters for gas storage in this field are within the range of the existing field parameters in Europe and America.